Karakteristik Sosiodemografi dan Health Related Quality of Life Pasien Rawat Jalan Diabetes Mellitus Tipe 2 pada Era JKN - Mita Restinia; Yusi Anggriani; Aries Meryta; Tri Kusumaeni (Jurnal Sains Farmasi & Klinis, 2016)
The aim of  study was carried out to determine differences of health related qualitiy of life (HRQoL) with sociodemographic characteristic in type 2 diabetes mellitus outpatiens at one of government hospital in Jakarta. It was a cross-sectional study conducted  from February  to April 2015. Total of samples were 83 patients. Male 31(37.4%) and female 52(62.6%). HRQoL associated with level education  was difference significantly (P<0.05).  Based on score of domain quality of life, female had higher score (69.82 ± 3.14) of frequency of symptoms domain than male (67.32 ± 4.50) (P<0.05). The oldest patients had the highest score (P<0.05) in domain of satisfaction. In contrast, the oldest patients had the the most decrease score (64.14 ± 4.03) in domain of frequency of symptoms (P<0.05). Patients of senior high school had lower score (60.17 ± 24.65) in domain of treatmant satisfaction than patients of  diploma/bachelor (78.78 ± 21.98). Score of domain of frequency of symptoms was higher on patients employed  than none (P<0.05). The household income did not influence all domain (P>0.05). Furthermore, diabetes duration affected both domain of satisfaction (P=0.005) and frequency of symptoms (P=0.00). In conclusion, only education level of characteristic sociodemographic had difference significantly to HRQoL among type 2 diabetes mellitus outpatients..